Drying kinetics of glutinous rice using an infrared irradiation technique - Dongbang, Watcharin; Nuantong, Weerapon (Engineering and Applied Science Research, 2018)
This study investigates the drying kinetics of glutinous rice using an infrared irradiation technique. The glutinous rice was dried at three infrared irradiation powers, 300, 400 and 500 W, with three thicknesses, 5, 10 and 15 mm. The glutinous rice was dried starting from an initial moisture content of 81% (wb) down to a final moisture content of 25% (wb). The results indicate that the drying kinetics depended on the drying temperature. The glutinous rice after drying at 300 W appeared lightest, while drying with the highest power, 500 W, it appeared darkest in color. Additionally, a layer thickness of 5 mm is accepable in the market and had the shortest time for drying, 104 to 194 minutes. The moisture ratio was fitted to determine the model parameters that can adequately describe the drying kinetics. The regression analysis results showed that the Page model was the best model based on its highest value of and its lowest values of and . The moisture diffusivity of glutinous rice was found to be in the range of 32.96 to 53.26 m²/s.